Bridging Equity Gaps in Maternal and NCD Services: Policy Priorities for Bangladesh's Evolving Health Landscape - Abdullaha Al Mamun (Health Science Reports, 2026)
ABSTRACT Background Over the past decade, Bangladesh has made significant gains in maternal and child health, driven by investments in community‐based services, education, and targeted public health interventions. However, disparities in service access and a growing burden of non‐communicable diseases (NCDs) continue to undermine the promise of universal and equitable care. Objective This perspective provides a policy‐oriented, interceptive synthesis of progress and persistent gaps in five critical domains—maternal care, child nutrition, family planning, immunization, and hypertension—by analyzing population‐level data from the Bangladesh Demographic and Health Surveys (BDHS) 2017–2018 and 2022. It aims to identify the systemic drivers of health inequity and offer evidence‐informed policy recommendations to bridge the divide between national averages and marginalized subgroups. Results Between 2017 and 2022, national gains in maternal care and stunting reduction were notable. However, these aggregate successes mask persistent disparities; access to skilled birth attendance and antenatal care remains heavily stratified by education and wealth, with gaps exceeding 40% in some cohorts. While immunization coverage has reached a stabilization phase, hypertension prevalence is rising, with control rates alarmingly low among rural, uneducated, and socioeconomically disadvantaged groups. This dual burden of stalled progress in traditional health domains and an increasing NCD burden highlights a critical misalignment between existing service delivery and the needs of an evolving population. Conclusion Bangladesh's health system must pivot from fragmented vertical programs toward an integrated, equity‐first model. Closing persistent gaps requires prioritizing NCD integration into primary healthcare, scaling digital registries to target “zero‐dose” children, and institutionalizing equity monitoring. Without a bold, equity‐driven transformation, these disparities will jeopardize the sustainability of past gains and compromise the country's ability to achieve universal health coverage.